Government Collaboration in Stunting Prevention Programme in Medan City - Nasution, Nabila Fahira; Trimurni, Februati (Formosa Journal of Multidisciplinary Research, 2024)
This research focuses on stunting prevention by looking at the level of collaboration between local governments in overcoming stunting in Medan City. Qualitative research methodology with a descriptive approach was used in this study. In-depth interviews and observations were used to collect primary data. Data and information on the collaboration process and the relationship between the government, private sector, and community were collected directly from each of the Medan City Government agencies involved. Secondary data were collected from authorised individuals and agencies in the form of papers, reports, and scientific publications in the form of processed data. Data analysis techniques included data reduction, data display, and conclusion drawing. The research findings show that government collaboration in stunting prevention in Medan City consists of three fundamental pillars in the notion of collaboration and, as a result, developed a coordination forum. In addition, although not statistically significant, the partnership process has resulted in a decrease in stunting rates. The Medan City government's efforts to learn and build trust with the community contributed to the success of the stunting prevention programme.